FRIENDS OF AFRICAN NURSING (CANADA) - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2011)
Friends of African Nursing (FoAN) is a small UK-based charity that was founded in 2001 to help teach and train perioperative nurses in Africa. Entirely volunteer run, FoAN aims to create a legacy of sustainable educational resources for African nurses working in difficult conditions and without access to continuing education. Most perioperative nurses in Africa work in clinical conditions that would be unrecognizable to Canadian nurses. Operating rooms in Africa may have concrete floors, broken or no equipment, outdated sutures and supplies, and a lack of important items such as gloves, dressings and scrub solutions. Perioperative education is limited or nonexistent – FoAN spent time in one country where that had been no perioperative education available for 36 years!